2000
DOI: 10.1034/j.1399-0004.2000.570410.x
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein B‐100 gene Xba I polymorphism and cholesterol gallstone disease

Abstract: The apolipoprotein (apo) B gene Xba I polymorphism is associated with alterations in serum lipids. Disturbances in serum lipids may be a risk factor for cholesterol gallstone disease. However, the relation between the Xba I polymorphism and cholesterol gallstones is unknown. This study was aimed at characterizing the polymorphism of the apo B gene Xba I in patients with gallbladder stones and the association of Xba I polymorphism with serum lipids. Xba I genotypes were measured by PCR-RFLP, and serum lipids as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 32 publications
4
35
1
1
Order By: Relevance
“…[9][10][11][12] However, the metabolic abnormalities underlying the supersaturation of bile and the formation of cholesterol gallstones induced by APO-B expression and/or polymorphisms are not yet fully understood. Thus the use of Apob 48/48 and Apob 100/100 mice should help to elucidate whether their expression levels are critical for cholesterol gallstone formation and to dissect the potential pathophysiological roles of each APO-B subtype, APO-B48 and APO-B100, in the formation of gallstones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12] However, the metabolic abnormalities underlying the supersaturation of bile and the formation of cholesterol gallstones induced by APO-B expression and/or polymorphisms are not yet fully understood. Thus the use of Apob 48/48 and Apob 100/100 mice should help to elucidate whether their expression levels are critical for cholesterol gallstone formation and to dissect the potential pathophysiological roles of each APO-B subtype, APO-B48 and APO-B100, in the formation of gallstones.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it has been found that polymorphisms in the apolipoprotein (APO)-B gene are associated with cholesterol gallstones in humans. [9][10][11][12] Therefore, we hypothesized that APO-B plays a major regulatory role in the response of biliary cholesterol secretion to high dietary cholesterol and contributes to the formation of cholesterol gallstones.…”
mentioning
confidence: 99%
“…Although not associated previously with PE or CHT, an APOB polymorphism (Thr2488Thr, CϾT) was added to the list of candidate polymorphisms for both diseases. The rationale for testing this polymorphism for PE consists in its association with serum level of LDL and apolipoprotein B 41,42 and the link between preeclampsia and increased serum concentration of small dense LDL. 4 For chronic essential hypertension, the rationale was based on the fact that an association of another polymorphism of APOB with blood pressure was reported previously.…”
Section: Association Study Of Candidate Genesmentioning
confidence: 99%
“…APOB XbaI polymorphism analysis was done as described previously (12). Allele was designated X + when restriction site for XbaI was present.…”
Section: Genotypingmentioning
confidence: 99%
“…This polymorphism of APOB has also been studied in gallstone patients. Han et al (12) found X + allele to be significantly higher, but in the Finnish population this polymorphism was not found to be associated with the gallstone disease (11,12).…”
Section: Introductionmentioning
confidence: 99%